The Electrification of Russia, 1880-1926 - Coopersmith, Jonathan (Cornell University Press, 1992)
≤p≥The Electrification of Russia, 1880-1926 is the first full account of the widespread adoption of electricity in Russia, from the beginning in the 1880s to its early years as a state technology under Soviet rule. Jonathan Coopersmith has mined the archives for both the tsarist and the Soviet periods to examine a crucial element in the modernization of Russia. Coopersmith shows how the Communist Party forged an alliance with engineers to harness the socially transformative power of this science-based enterprise. A centralized plan of electrification triumphed, to the benefit of the Communist Party and the detriment of local governments and the electrical engineers. Coopersmith's narrative of how this came to be elucidates the deep-seated and chronic conflict between the utopianism of Soviet ideology and the reality of Soviet politics and economics.